Increased attentional network functioning related to symptom severity measures in females with irritable bowel syndrome. Issue 9 (19th June 2015) - Hubbard, C. S.; Hong, J.; Jiang, Z.; Ebrat, B.; Suyenobu, B.; Smith, S.; Heendeniya, N.; Naliboff, B. D.; Tillisch, K.; Mayer, E. A.; Labus, J. S.
Abstract Background Increased attention to gastrointestinal (GI) symptoms and disease‐specific contexts may play an important role in the enhanced perception of visceral stimuli frequently reported in patients with irritable bowel syndrome (IBS). In this study, we test the hypothesis that altered attentional mechanisms underlie central pain amplification in IBS. Methods To evaluate brain networks that support alerting, orienting, and executive attention, we employed the attention network test (ANT), a modified flanker task which measures the efficiency of functioning of core attentional networks, during functional magnetic resonance imaging in 15 IBS patients (mean age = 31 [11.96]) and 14 healthy controls (HCs; mean age = 31 [10.91]). Key Results Patients with IBS, compared to HCs, showed shorter reaction times during the alerting and orienting conditions which were associated with greater activation of anterior midcingulate and insular cortices, and decreased activity in the right inferior frontal junction and supplementary motor cortex. Patients also showed activation in the dorsal medial prefrontal cortex and concurrent thalamic deactivation during the executive control portion of the ANT relative to HCs, but no group difference in reaction times were found. The activity in brain regions showing group differences during the ANT were associated with measures of GI‐specific anxiety, pain catastrophizing, and fear of uncertainty. In IBS, activity in the anterior midcingulate during alerting correlated with duration of GI‐symptoms and overall symptom severity. Conclusions & Inferences Together, these results suggest that IBS patients have specific abnormalities in attentional network functioning and these deficits may underlie symptom‐related anxiety, hypervigilance, and visceral hypersensitivity.